The legal field as battleground for social struggle - Veronica Pecile (Oñati Socio-Legal Series)
Scepticism towards law’s potential of fostering social change has been widespread in critical theory and contributed to strengthen social movements’ mistrust vis-à-vis the use of legal tools to advance their claims. Such “anti-law” posture is based on the assumption that law would formalise existing relations of domination and posits the need for a political praxis liberated from “legalistic drifts”. This article discusses how legal tactics in favour of social change have been employed by social movements exerting a counter-hegemonic use of law in the post-2008 economic crisis conjuncture. The example of the struggle for the commons will be analysed as paradigmatic of how the interests of the marginalised can be protected by resorting to existing property arrangements, and how it is possible to reclaim law from the margins.